Epileptic seizure clustering and accumulation at transition from activity to rest in GAERS rats - Tran, Hieu; Mahzoum, Reda El; Bonnot, Agnès; Cohen, Ivan (Frontiers in Neurology, 2024)
Knowing when seizures occur may help patients and can also provide insight into epileptogenesis mechanisms. We recorded seizures over periods of several days in the Genetic Absence Epileptic Rat from Strasbourg (GAERS) model of absence epilepsy, while we monitored behavioral activity with combined head accelerometer (ACCEL), neck electromyogram (EMG), and electro-oculogram (EOG). The three markers consistently discriminated states of behavioral activity and rest. Both GAERS and control Wistar rats spent more time in rest (55-66%) than in activity (34-45%), yet GAERS showed prolonged continuous episodes of activity (23 vs 18 min) and rest (34 vs 30 min). On average, seizures lasted 13s and were separated by 3.2min. Isolated seizures were associated with a decrease in the power of the activity markers from steep for ACCEL, to moderate for EMG and weak for EOG, with ACCEL and EMG power changes starting before seizure onset. Seizures tended to occur in bursts, with the probability to be seizing significantly increased around a seizure in a window of +/-4 min. Furthermore, the seizure rate was strongly increased, for several minutes, when transiting from activity to rest. These results point to mechanisms that control behavioral state as determining factors of seizure occurrence.